Face au cyclone Irma ! Le rôle des populations dans la gestion de la crise à Saint-Martin (Petites Antilles, îles du Nord) - Stéphanie Defossez; Monique Gherardi (EchoGéo)
The hurricane season 2017 in the North Atlantic was intense. The events recalled the exposure of the West Indies to these phenomena sometimes devastating, such as the cyclone Irma which caused heavy losses on the French islands of Saint-Martin and Saint-Barthélemy. The post-event phase sometimes gives rise to an experience feedback (RETEX), which reports on the steps and management processes of the event. RETEX is widely conducted with institutions but leaves to hear the people. This study is based on a scientific RETEX in which the individual dimension of crisis management is integrated, by asking to what extent do individuals participate (or not) in crisis management (directly and indirectly) and how? The scientist team went to meet populations to assess how they lived and prepared themselves to cope with TC Irma in order to present the invest of populations in crisis management. The acknowledgment of populations about natural hazards is fine, and they also know recommendations to cope with cyclone. However, TC Irma was more strong that the reference event (Luis in 1955) for which the populations were prepared. Damage revealed and/or increased existing vulnerabilities which raise the question of built back processes.